ANALISIS PERILAKU TOXIC RELATIONSHIP DI SMA NEGERI 14 GOWA: Gambaran perilaku toxic relationship - Siti khaerunnisyah Darwiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the manifestation of toxic relationship behaviors in a female high school student, identify the contributing factors, and examine the resulting impacts on academic, emotional, and social functioning. Employing a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving the student, the school counselor, homeroom teacher, parents, and peers. The findings reveal that toxic relationship patterns are demonstrated through excessive jealousy, heightened worry, controlling tendencies, and repetitive conflicts. Contributing factors arise from internal aspects such as emotional exhaustion, disrupted self-regulation, and unstable emotional attachment, as well as external aspects including permissive parental monitoring, unsupportive school dynamics, and peer influence. The impacts include decreased academic motivation, socio-emotional withdrawal, and impaired concentration. The intervention, conducted using the Solution Focused Brief Counseling (SFBC) approach, resulted in positive changes in the student’s emotional regulation, relational boundaries, and learning consistency.